Organizational commitment and teaching performance in the Urban Educational Institutions of the district of Las Piedras, Tambopata, Madre de Dios, 2018 - Estrada Araoz, Edwin Gustavo (2020)
Abstract The objective of this research was to establish the relationship between organizational commitment and teaching performance in the Urban Educational Institutions of the Las Piedras district - 2018. The type of research was non-experimental, the cross-sectional descriptive descriptive design. The study population was formed by the 106 teachers who work in the Urban Educational Institutions of the district of Las Piedras and the sample by 83 teachers which was obtained through a stratified probabilistic sampling. To collect information, the Meyer and Allen Organizational Commitment Questionnaire adapted in Peru by Oscar Martín Rivera Carrascal and the Teaching Performance Questionnaire were used. The data collected were consolidated in a database to be processed through the Statistical Package for Social Sciences SPSS version 22. The results found indicate that 48.2% of teachers have a high level of organizational commitment, 60.2 % of teachers have a satisfactory level of performance and in terms of the contrast of the general hypothesis, it was statistically found that there is a strong, direct and significant relationship between the variables organizational commitment and teacher performance. Spearman's rho correlation coefficient is 0.724 with a p-value below the level of significance (p = 0.000 <0.05). Finally, it is concluded that as long as teachers present a greater organizational commitment, they will perform better and vice versa.